Soils, Plants and Clay Minerals Mineral and Biologic Interactions - Velde, Pierre. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book considers the inter-relations between plants and minerals in an entirely new way, in that it introduces the notion of eco-engineering: i.e. the manipulation of the mineral world by the living world to the ends of the living world. These inter-relations are the basis for traditional agriculture and should be the basis for new, ecologically oriented land management disciplines, including agriculture itself. These relations also have an impact on surface geochemistry and determine pollution problems. A better understanding of this concept will lead to a renewed consideration of surface environmental problems.